Observations and discoveries of supernova remnants with GMRT. Issue Volume 9:Issue S296(2013) (29th January 2014) - Roy, Subhashis; Pal, Sabyasachi
Abstract: We have measured HI absorption distance to the youngest Galactic supernova remnant G1.9+0.3. Absorption by known anomalous velocity features near the Galactic centre (GC) puts a lower limit on its distance from Sun as 10 kpc, 2 kpc further away from the GC. We have found a small diameter (1.6′) shell like structure G354.4+0.0, that shows polarised emission in the NVSS. Based on its morphology, angular size, HI distance and its spectrum between 1.4 GHz and 330 MHz, it is perhaps the second youngest SNR in the Galaxy that is expanding in a dense environment of an HII region surrounding it. Our pilot observation of the inner Galactic 4th quadrant within 337° < l < 354° with a fixed Galactic latitude of 0.37° has confirmed G345.1−0.2 as an SNR.